Inocybe hamadryadis (Inocybaceae, Agaricales), a new smooth-spored species from Europe and West Asia - Rodríguez-Campo, Francisco J.; Bandini, Ditte; Olariaga, Ibai (Phytotaxa, 2023)
Inocybe hamadryadis sp. nov. is described and a detailed description, colour photographs, microdrawings and photographs of the microscopic features are provided. The type was found under Quercus ilex and Cistus ladanifer in Mediterranean habitat in Spain, but its distribution is throughout Europe and the West Asia. Inocybe hamadryadis is characterized by a finely textured, pale to dark brown or chestnut brown pileus with a faintly greyish velipellis, smooth basidiospores, hymenial cystidia with sinuous walls and caulocystidia only near the extreme apex of the stipe. Our analyses of the ITS and LSU regions, including coded indel information, indicate that I. hamadryadis is closely related to I. tenuicystidiata, from which it differs in several morphological features, such as the smaller basidiospores on average and the shorter caulocystidia.